Polymorphisms of the vitamin D receptor, infant growth, and adult bone mass. - Keen, R; Egger, P; Fall, C; Major, P; Lanchbury, J; Spector, T; Cooper, C (1997)
Family and twin studies have demonstrated a strong genetic component to the development of peak bone mass. Early fetal and infant environment has also been shown to influence bone mass through an effect on skeletal size and mineral content. We report a retrospective study that has examined whether early infant growth is regulated by genetic factors shown to be associated with bone mass. We have determined the vitamin D receptor (VDR) gene alleles for 66 women (mean age 65.5 years) on whom detailed birth records were available. There was a statistically significant trend (P = 0.04) for VDR genotype against weight at the age of 1 year, with the "tt" homozygote group having 7% higher weight. We conclude that early fetal or infant environment may interact with an individual's underlying genotype to program early skeletal growth, and that this may track through later life to influence adult characteristics. Further prospective studies are required, however, to fully clarify the precise environmental and genetic mechanisms underlying these findings.